The Androgen Receptor in Breast Cancer - Giovannelli, Pia; Di Donato, Marzia; Galasso, Giovanni; Di Zazzo, Erika; Bilancio, Antonio; Migliaccio, Antimo (Frontiers in Endocrinology, 2018)
Breast cancer (BC) is a hormone-related tumor. Despite the progress in BC therapy, this disease still remains the most common cancer amongst women around the world. This is likely due to the amazing BC heterogeneity. Accumulating evidence suggests a role for androgen signaling in BC. Nevertheless, a precise understanding of the mechanism of androgen action in this disease remains a challenging puzzle. Androgen receptor (AR) is often expressed in BC and several studies suggest that its role depends on the tumor microenvironment as well as the relative levels of circulating estrogens and androgens. However, the AR function in BC is still conflicting. Although AR expression is often associated with a favorable prognosis in ERα-positive (ERα+) BC, many findings suggest that, in some instances, high levels of AR can contribute to the therapy-resistance. Again, in ERα negative BC (ERα-), AR is mainly expressed in tumors with apocrine differentiation and a lower Nottingham grade. Moreover, AR stimulates cellular proliferation in triple negative breast cancer (ERα -, PgR -, HER-2-Neu -). This finding is substantiated by the observation that high levels of circulating androgens are associated with an increased risk of developing BC in postmenopausal woman. Treatment of ERα- BC with AR antagonists, such as bicalutamide or enzalutamide, reduces, indeed, the tumor growth. In this review, we will analyze the putative role of AR in BC. Emerging therapies based on the use of new agonists or antagonists or inhibitors will be here discussed.